Exploring The Influence of Implementing an Independent Curriculum and Learning Quality on Learning Effectiveness: Does the Mediation of School Infrastructure Matter? - Rahmawati, Maulida Novi; Ahmadi, Ahmadi; Daryono, Rihab Wit (JURNAL TARBIYAH, 2024)
The study focuses on the impact of infrastructure in facilitating the implementation of a student-centered, problem-solving curriculum aimed at developing 21st-century skills. By surveying 70 teachers at MTs Al-Islam Ponorogo using a Likert scale questionnaire, the research found that the independent curriculum significantly influences infrastructure and learning effectiveness. Moreover, infrastructure acts as a mediator between the curriculum and mutual learning. These results underscore the crucial role of infrastructure in enhancing learning outcomes through student-centered approaches.Practical implications include the need for relevant curricula that cater to students' needs and enhance learning experiences. The study advocates for program development that prioritizes strengthening infrastructure, integrating independent curriculum implementation, and promoting mutual learning to boost overall learning effectiveness. By emphasizing the importance of facilities in supporting educational initiatives, the research highlights the significance of creating conducive environments for effective teaching and learning practices.